The Role of Youth in the Stunting Prevention via Podcast in Karawang Regency 2020 - Rahayu, S.; Rahayu, Maria Alia; Apriningrum, Nelly; Chairudin, Chairudin; Asep, Asep; Ulya, Neng (International Journal Labs, 2022)
Podcasts are audio recordings that can be listened to by the general public through internet media. Unlike the radio which must be done and broadcast live at a certain frequency. Podcasts can be used as a medium of information related to stunting podcast management by teenagers is expected to better reach stunting prevention goals appropriately. This study aims to provide knowledge about stunting prevention and information dissemination skills about stunting prevention through podcasts in adolescents. The question and answer lecture method is used in the presentation of knowledge, while podcast training uses the demonstration method. This study was conducted from August to October 2020, with a number of respondents 10 adolescent participants. Through this service activity, increasing adolescent knowledge about stunting and spreading stunting information through podcasts to the knowledge of all respondents in the good category (100%), adolescent experience and skills in podcast management became quite 10% and good 90%.